DISKURSUS THE MALAYS DAN MALAYNESS : PERSPEKTIF HERMENEUTIKA FILOSOFIS GADAMER - I Irwandra; Misnal Munir; Heri Santoso (Sosial Budaya, 2018)
This paper aims to discuss informatively and critically-philosophically the two main discourses, namely The Malays and Malayness, which in the context of history and the dynamics of Malay culture are suggested to overlap, so that it is often misunderstood. The use of Gadamer philosophical hermeneutics as a media in analyzing data in this study is expected to be able to find new understanding of the two themes above, especially in the context of strengthening values and forming culture-based characters. The scrutiny and review of the treasures of Malay culture found that the Malay culture which stretched in a span of three periods, the past-present-future found a starting point as a place for cultural assessment, especially after the entry and development of Islam in the Malay-Indonesian Archipelago. The intended point is the Malay Culture "which is called the fresh culture. "Culture Appearance" takes place continuously and tracks in almost every practice of life without negating the old belief patterns (customs and traditions) that first enter and come into contact with the dynamics of people's lives.